The effect of 1,25-dihydroxyvitamin D3 on methylation and expression of the human renin gene - Govender, Daniesha (My University, 2022)
Blood pressure has long been associated with vitamin D suggesting a link between vitamin D deficiency and hypertension progression. Renin, encoded by the REN gene, is an essential enzyme in the renin-angiotensin-aldosterone system (RAAS) which is responsible for the maintenance of blood pressure homeostasis. The active metabolite of vitamin D, 1,25dihydroxyvitamin D3 (1,25(OH)2D3) mediates almost all its functions when bound to its nuclear receptor, the vitamin D receptor (VDR). Transcriptional regulation of REN has been linked to enhancer-promoter crosstalk, cAMP response element-binding protein (CREB), 1,25(OH)2D3-bound VDR and a less well-characterised intronic silencer element. We therefore hypothesised that differential DNA methylation affects REN expression and influenced by 1,25(OH)2D3. A VDR + and VDR - HEK293 cell culture model, which readily expressed REN, was established, and used to elucidate the effect of 1,25(OH)2D3 on REN methylation and expression, as quantified by matrix-assisted laser desorption ionisation- time of flight mass spectrometry (MALDI-TOF MS) and reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR), respectively. In vitro 1,25(OH)2D3 supplementation (10 nM) induced changes in DNA methylation within the REN enhancer and silencer regions, which was coupled to a significant reduction in REN expression (P < 0.010) in the VDR + samples. In addition, 1,25(OH)2D3 increased the expression of VDR (P < 0.050), and that of the ten-eleven translocation enzyme encoding genes, TET1 (P < 0.050) and TET2 (P < 0.050); responsible for DNA demethylation. The induced expression of both VDR and the demethylating agents, TET1 and TET2, suggest that 1,25(OH)2D3 may induce active loci specific demethylation events at the REN silencer. Thus, it appears that both the enhancer and silencer elements are regulated by DNA methylation, which is influenced by 1,25(OH)2D3, and play an essential role in regulating REN expression.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Molecular and Cell Biology to the Faculty of Science, School of Biology, University of the Witwatersrand, Johannesburg, 2022